2017
DOI: 10.21475/ajcs.17.11.02.p269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ABA on colour of berries, anthocyanin accumulation and total phenolic compounds of ‘Rubi’ table grape (Vitis vinifera)

Abstract: The color of the berry grapes is due to existence of anthocyanins and their accumulation seems to be regulated, at least in part, by abscisic acid. Therefore, exogenous applications of this regulator may increase the anthocyanins concentration in the grapes skin. The objective of this study was to evaluate the effect of abscisic acid on the color of berries and in the anthocyanin accumulation and total phenolic compounds of 'Rubi' grapes. The 'Rubi' grape (Vitis vinifera) variety was studied in the sixth year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
8
19
0
Order By: Relevance
“…The synthesis of anthocyanins can occur, constantly, from the beginning of maturation to harvest, as well as during the first half of maturation (Mullins et al, 1992), which justifies the positive effect of S-ABA application on two grape ripening stages. Several studies have demonstrated that the exogenous application of S-ABA increases the anthocyanin content in grapes (Ban et al, 2003;Yamamoto et al, 2015, Domingues Neto et al, 2017. It is possible to state that, with the results obtained in this study and those already available in the literature, that the S-ABA triggers the secondary metabolism of 'Niagara Rosada' grapes and other grape cultivars, specifically the anthocyanin biosynthesis, which is the pigment that imparts a pink/purple color on fruits, flowers and vegetables.…”
Section: Concentrations Of S-abasupporting
confidence: 69%
See 2 more Smart Citations
“…The synthesis of anthocyanins can occur, constantly, from the beginning of maturation to harvest, as well as during the first half of maturation (Mullins et al, 1992), which justifies the positive effect of S-ABA application on two grape ripening stages. Several studies have demonstrated that the exogenous application of S-ABA increases the anthocyanin content in grapes (Ban et al, 2003;Yamamoto et al, 2015, Domingues Neto et al, 2017. It is possible to state that, with the results obtained in this study and those already available in the literature, that the S-ABA triggers the secondary metabolism of 'Niagara Rosada' grapes and other grape cultivars, specifically the anthocyanin biosynthesis, which is the pigment that imparts a pink/purple color on fruits, flowers and vegetables.…”
Section: Concentrations Of S-abasupporting
confidence: 69%
“…Several studies suggest that exogenous applications of ABA increase the anthocyanin content in the skin of colored grapes, surpassing even the ethephon, playing a vital role in the activation of flavonoids (Cantín et al, 2007;Peppi et al, 2007;Sandhu et al, 2011;Roberto et al, 2013;Koyama et al, 2014a;Domingues Neto et al, 2017).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%
See 1 more Smart Citation
“…The actual yield was estimated during the harvest period by measuring the total number of bins per cell and multiplying it with the average bin weight of the harvested table grapes. Fifty berries were randomly taken in each vineyard cell at harvest by sampling five berries from one cluster per grapevine from a total of ten grapevines to assess berry and must parameters [48]. Berry diameters were estimated using the image analysis software, ImageJ 1.46r (Research Services Branch, NIMH, Bethesda, MD, USA).…”
Section: Spectral Vegetation Index Equation Bibliographymentioning
confidence: 99%
“…The efficiency of exogenous application of ABA has been demonstrated in the synthesis and accumulation of anthocyanins (polyphenols) in the peel of many grape cultivars [8] [9] [10] [11], as well as it provides uniformity of color, improves the quality of the treated grapes [8] [12], and increase the phenolic compounds contents [11] [13]. Anthocyanin performs an important role in the color and in the sensorial characteristics of fruits and vegetables, beyond its protective effects against certain types of cancer and cardiovascular diseases [14] [15].…”
mentioning
confidence: 99%